2015
DOI: 10.1123/jpah.2014-0136
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the SenseWear Armband as a Measure of Sedentary Behavior and Light Activity

Abstract: The SWA and IC EE rates were strongly correlated during sedentary and light activity office behaviors. However, the SWA may under predict EE during office work (standing or sitting) and when standing motionless, making it slightly less sensitive than IC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…SWA has limitations and is less sensitive when metabolic activity of very light physical work, such as office work is recorded [21,47]. Physical activity may therefore have been underestimated for office workers (NO subgroup) in our study.…”
Section: Discussionmentioning
confidence: 94%
“…SWA has limitations and is less sensitive when metabolic activity of very light physical work, such as office work is recorded [21,47]. Physical activity may therefore have been underestimated for office workers (NO subgroup) in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Data were accepted when the average on-body measuring time was at least 1368 minutes per day (95% of a 24-hour bout). The SWA has been validated in clinical (Van Remoortel et al, 2012) and non-clinical (Reece et al, 2015) populations.…”
Section: Physical Activity and Sedentary Behaviour: Sensewear Armbandmentioning
confidence: 99%
“…SW monitors have been extensively evaluated for validity of measures of EE, with several recent studies using the SWm. 1622 To our knowledge, only Reece and colleagues 19 specifically explored SWm measures of time spent in lower intensity activity; their study reported very high accuracy (89%) for SWm measures of time spent across a spectrum of sedentary, light, and moderate activities.…”
mentioning
confidence: 98%